2015
DOI: 10.1111/1365-2664.12442
|View full text |Cite
|
Sign up to set email alerts
|

Reducing soil erosion by improving community functional diversity in semi‐arid grasslands

Abstract: Summary1. Great efforts have been made to control soil erosion by restoring plant communities in degraded ecosystems world-wide. However, soil erosion has not been substantially reduced mainly because current restoration strategies lead to large areas of mono-specific vegetation, which are inefficient in reducing soil erosion because of their simple canopy and root structure. Therefore, an advanced understanding of how community functional composition affects soil erosion processes, as well as an improved rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 47 publications
3
73
0
1
Order By: Relevance
“…So, Control plots and Robinia plots had different species composition, but Control plots of all ages had lower cover values but higher number of species than Robinia plots, mainly of herbaceous perennial species that contributed most to the soil resistance to erosion (Zhu et al, 2015), and also Control plots of the same age were more homogenous in composition than Robinia plots, accordingly with the values of b-diversity. These differences between Control and Robinia plots may be the consequence of the effects that R. pseudoacacia plantations have on micro-environmental conditions.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…So, Control plots and Robinia plots had different species composition, but Control plots of all ages had lower cover values but higher number of species than Robinia plots, mainly of herbaceous perennial species that contributed most to the soil resistance to erosion (Zhu et al, 2015), and also Control plots of the same age were more homogenous in composition than Robinia plots, accordingly with the values of b-diversity. These differences between Control and Robinia plots may be the consequence of the effects that R. pseudoacacia plantations have on micro-environmental conditions.…”
Section: Discussionmentioning
confidence: 91%
“…Later, in 1999, the Chinese government implemented the ''Grain for Green" policy (conversion of steep cultivated land to forest and grassland) to control soil erosion, and again R. pseudoacacia was widely used for this purpose with the result that more than 70,000 ha were afforested with this species from 1950 to 2005 in the hilly Loess Plateau (Guo et al, 2005). However, in the past years, several negative effects of R. pseudoacacia plantations on soil properties have been described, questioning its beneficial role (Jiang et al, 2013;Zhu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Different erosion processes and steps have different traits, which can be affected by different plant functional traits (Zhu et al, 2015). Soil erosion types are thus meaningful for studying the relationship between soil erosion and plant diversity or plant functional diversity.…”
Section: Introductionmentioning
confidence: 99%
“…As noted by Zhu et al (2015), the restoration strategies led to large areas of mono-specific vegetation in P 2 , and streamflow had not been substantially conserved by revegetation. The use of a sediment-trapping dam is a long-standing approach to controlling sediment yields, and it contributed approximately 60-70% of sediment load reduction during P 2 across eroding gullies and smaller tributaries (Ran et al, 2000;Zhang et al, 1997;Zheng, 2006).…”
Section: The Potential Changes In Sediment Loadmentioning
confidence: 97%
“…Plot experiments showed that soil and water were significantly reduced by 54% and 79% when the vegetation coverage by grasses was 20% and 40%, respectively (Cai et al, 1992;Zeng and Ma, 1990). As noted by Zhu et al (2015), the restoration strategy in the 2000s was improved by incorporating community functional diversity into the restoration design. It was noted that vegetation recovery in the Loess Plateau was the best in China and statistically significant in recent years (Lü et al, 2003).…”
Section: Phases Of Sediment Yield Reductionmentioning
confidence: 99%